MOFs as Adsorbents for Low Temperature Heating and Cooling Applications - Henninger, Stefan K; Habib, Hesham A; Janiak, Christoph (Journal of the American Chemical Society, 2009)
The 3D metal−organic framework (MOF) 3 ∞{[Ni3(μ3-btc)2(μ4-btre)2(μ-H2O)2]·∼22H2O} is found to be a reversibly dehydratable−hydratable water-stable MOF material with a large loading spread of 210 g/kg as a candidate for solid adsorbents in heat transformation cycles for refrigeration, heat pumping, and heat storage.